Phytochemical Investigation & Antimicrobial Activity of Methanolic Extract of Sonneratia apetala Buch-Ham. Areal parts - Panda, Sangram Keshari (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT The present study was attempt to investigate the phytochemical constituents and to explore & antimicrobial activity of methanolic extracts of Sonneratia apetala arial parts. all the tests for phytochemical constituents of methanolic extracts of S. apetal,were found tobe presence of terpenoid , steroid, alkaloid , flavonoid ,tannins, saponins& polysaccharide Antimicrobial activities of the plant extracts were determined by the well diffusion method. In vitro screening of S. apetala plant extracts showed species specific activity ininhibiting the growth of bacteria &fungi.The tested extract showed to varying degrees of antibacterial potential against tested gram-negative as well as gram-positive bacteria.These promising findings suggest antibacterial activity of the plant material. Methanol extracts showed good activity against all the pathogens, The anti-microbial activity of the methanolic extract of S. apetala at 10 mg/ml was found to be dose dependant and significant compare to standard anti-microbial agent ciprofloxacin & clotrimazol at 10Âµ g/disc.